2014
DOI: 10.1149/2.0741409jes
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Operation of Rechargeable High Temperature Solid Oxide Batteries

Abstract: A novel rechargeable high temperature metal -air battery based on the planar solid oxide fuel cell technology has been developed [H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…It appears that its performance, round-trip efficiency, and cycle stability require further improvement. In long-term charging and discharging experiments, these batteries [25] demonstrate average degradation, which leads to more than 40% charging material after 10,000 charging cycles. On average, as it is analysed, solid oxide fuel cell materials also degrade to a certain degree [26].…”
Section: Smart Grids and Energy Hydrogen Storagementioning
confidence: 99%
“…It appears that its performance, round-trip efficiency, and cycle stability require further improvement. In long-term charging and discharging experiments, these batteries [25] demonstrate average degradation, which leads to more than 40% charging material after 10,000 charging cycles. On average, as it is analysed, solid oxide fuel cell materials also degrade to a certain degree [26].…”
Section: Smart Grids and Energy Hydrogen Storagementioning
confidence: 99%
“…There are two main reasons for this relatively balanced redox reaction: 1) a more balanced H 2 For the 800 o C-battery, the effect of e o on battery's cycle performance is shown in Fig.5 (b) . It is worth mentioning that the nature of Nernst potential being proportional to ln(P H2O /P H2 ) not directly to P H2O /P H2 implies that it is more sensitive to P H2 at higher DoD.…”
Section: The Effect Of Current Densitymentioning
confidence: 99%
“…The battery was continuously cycled 100 times and a gradual decline in performance was observed. Leonide et al [28] reported the results of a long-term operation test of a short stack at a constant temperature of 800 o C. They observed a decrease in the discharge capacity but nearly 40% of the storage metal remained active even after 10,000 cycles. Although there are still problems to be solved to minimize the degradation, these experimental results are generally encouraging.…”
Section: Introductionmentioning
confidence: 99%